Implementation of drift velocities and currents in SOLEDGE2D–EIRENE. (August 2017) - Bufferand, H.; Baudoin, C.; Bucalossi, J.; Ciraolo, G.; Denis, J.; Fedorczak, N.; Galassi, D.; Ghendrih, Ph.; Leybros, R.; Marandet, Y.; Mellet, N.; Morales, J.; et al.
Highlights: Derivation of electric potential equation for the transport code SOLEDGE2D–EIRENE. Inclusion of drifts and currents in SOLEDGE2D–EIRENE. Tests in simple configuration. Application to WEST divertor configuration in Forward and Reverse B field. Abstract: In order to improve cross-field transport description, drifts and currents have been implemented in SOLEDGE2D–EIRENE. The derivation of an equation for the electric potential is recalled. The resolution of current equation is tested in a simple slab case. WEST divertor simulations in forward-B and reverse-B fields are also discussed. A significant increase of ExB shear is observed in the forward-B configuration that could explain a favorable L-H transition in this case.